Engage with knowledgeable experts and get accurate answers on IDNLearn.com. Our experts provide timely, comprehensive responses to ensure you have the information you need.
Sagot :
To determine the [tex]$x$[/tex]-intercepts of the quadratic function [tex]\( g(x) = -2(x-4)(x+1) \)[/tex], we need to find the values of [tex]\( x \)[/tex] for which [tex]\( g(x) = 0 \)[/tex].
Let's set the function equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ g(x) = -2(x-4)(x+1) = 0 \][/tex]
The product of two factors is zero if at least one of the factors is zero. Therefore, we need to solve the equations:
[tex]\[ (x-4) = 0 \][/tex]
and
[tex]\[ (x+1) = 0 \][/tex]
Solving these equations for [tex]\( x \)[/tex]:
1. For [tex]\( (x-4) = 0 \)[/tex]:
[tex]\[ x = 4 \][/tex]
2. For [tex]\( (x+1) = 0 \)[/tex]:
[tex]\[ x = -1 \][/tex]
Thus, the [tex]\( x \)[/tex]-intercepts of the function [tex]\( g(x) = -2(x-4)(x+1) \)[/tex] are [tex]\( (4, 0) \)[/tex] and [tex]\( (-1, 0) \)[/tex].
So, the correct answer is:
D. [tex]\((4,0)\)[/tex] and [tex]\((-1,0)\)[/tex]
Let's set the function equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ g(x) = -2(x-4)(x+1) = 0 \][/tex]
The product of two factors is zero if at least one of the factors is zero. Therefore, we need to solve the equations:
[tex]\[ (x-4) = 0 \][/tex]
and
[tex]\[ (x+1) = 0 \][/tex]
Solving these equations for [tex]\( x \)[/tex]:
1. For [tex]\( (x-4) = 0 \)[/tex]:
[tex]\[ x = 4 \][/tex]
2. For [tex]\( (x+1) = 0 \)[/tex]:
[tex]\[ x = -1 \][/tex]
Thus, the [tex]\( x \)[/tex]-intercepts of the function [tex]\( g(x) = -2(x-4)(x+1) \)[/tex] are [tex]\( (4, 0) \)[/tex] and [tex]\( (-1, 0) \)[/tex].
So, the correct answer is:
D. [tex]\((4,0)\)[/tex] and [tex]\((-1,0)\)[/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.